2006
DOI: 10.1590/s0101-20612006000400017
|View full text |Cite
|
Sign up to set email alerts
|

Isotermas de adsorción en harina de maíz (Zea mays L.)

Abstract: RESuMENEl objetivo de este trabajo fue determinar las isotermas de adsorción de humedad de harina de maíz a tres temperaturas (7, 22 y 45 °C) para el rango de a w entre 0,10 y 0,95. Las isotermas se modelaron utilizando siete ecuaciones comúnmente aplicadas en alimentos. La calidad de ajuste se evaluó con el coeficiente de regresión (r 2 ) y el porcentaje de error medio relativo (% E), en función de los cuales se observó que los modelos propuestos por GAB, Oswin y Halsey ajustaron de mejor manera los datos exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
1
16
1
9
Order By: Relevance
“…Some of the above-mentioned studies, found isotherm crossovers due to the effect of temperature at elevated water activities (usually above 0.75) when thymol was used as an antimicrobial agent. 14,16,17,[20][21][22] Other studies did not show isotherm crossovers but no sorption data was presented at elevated temperature for water activities above 0.80-0.85 and therefore possible isotherm crossovers were not evidenced. [10][11][12] Some of these products contained a significant fat content (sardines, chickpea, corn flour, sesame flour, distillers dried grains, and oat flour), therefore absorption of thymol by fat in the product was possible since thymol has affinity for lipids, being soluble in organic compounds as indicated previously.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some of the above-mentioned studies, found isotherm crossovers due to the effect of temperature at elevated water activities (usually above 0.75) when thymol was used as an antimicrobial agent. 14,16,17,[20][21][22] Other studies did not show isotherm crossovers but no sorption data was presented at elevated temperature for water activities above 0.80-0.85 and therefore possible isotherm crossovers were not evidenced. [10][11][12] Some of these products contained a significant fat content (sardines, chickpea, corn flour, sesame flour, distillers dried grains, and oat flour), therefore absorption of thymol by fat in the product was possible since thymol has affinity for lipids, being soluble in organic compounds as indicated previously.…”
Section: Introductionmentioning
confidence: 93%
“…Some authors have used thymol as an antimicrobial agent in food moisture sorption isotherm determinations by the SG technique in temperature ranges that included elevated temperatures: Menkov 10 in lentil seeds (5-60°C); Sablani et al 11 in freeze-dried sardines (25-50°C); Moreira et al 12 in fresh chickpea (25-45°C); Durakova and Menkov 13 in rice flour (10-30°C); Durakova and Menkov 14 in chickpea flour (10-40°C); Cassini et al 15 in texturized soy protein (10-40°C); Vega-Gálvez et al 16 in corn flour (7 to 45°C); Menkov and Durakova 17 in sesame flour (10-40°C); Goula et al 18 in spray-dried tomato pulp (20-70°C); Vega-Gálvez et al 19 in Chilean papaya (5-45°C); Ganesan et al 20 in distillers dried grains (10-40°C); Perdomo et al 21 in cassava starch (5-45°C) and Brett et al 22 in oat and rice flours (5 to 45°C). Some of the above-mentioned studies, found isotherm crossovers due to the effect of temperature at elevated water activities (usually above 0.75) when thymol was used as an antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…(4)). Such experimental data, were taken from literature and previous work [20,21], and fitted using the Oswin model, which has been reported to provide satisfactory fitting in several works [22][23][24][25]: (8) where the fitting parameters A and B are specific to each material.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In this study, 10 mathematical models were used to describe the adsorption isotherms of chitosan films at different temperatures (Aviara et al, 2004;Ayala Aponte et al, 2011;Furmaniak et al, 2007;Gálvez et al, 2006;Timmermann et al, 2001). From these 10 equations (Equations 1-10; Table 2), 5 are the original models and 5 are modified versions of each model where the temperature is taken into account.…”
Section: Mathematical Moisture Sorption Modelsmentioning
confidence: 99%
“…In the case of chitosan, when it is hydrated at low values of RHeq (< 50%) the rate of relaxation of the solvent Table 2. Isotherm models used for experimental data fitting (Aviara et al, 2004;Ayala Aponte et al, 2011;Furmaniak et al, 2007;Gálvez et al, 2006;Timmermann et al, 2001 Where a w is water activity, X is the moisture content on a dry base and T is temperature.…”
Section: Moisture Adsorption Isothermsmentioning
confidence: 99%